Efektivitas Penerapan Video Pembelajaran pada Mata Pelajaran Dasar Listrik Elektronika - Muhammad Faiz Al Hafizh Putra; Mukhlidi Muskhir (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2022)
This study aims to find out how effective the use of learning videos is on the learning outcomes of smk class X TITL students in basic subjects of electronic electricity which are material on the basic theory of electricity. This research was conducted on class X TITL 1 students at SMK Negeri 5 Padang. Data collection is carried out by providing pre-test and post-test questions in the form of 20 multiple-choice questions with 4 answer choices. The number of samples used in this study was 29 students. To see the effectiveness of the use of learning videos by using hypothesis test data analysis and n-gain. The results of the data calculation were obtained with a test value of 0.001 and an n-gain score of 0.69. It is known that in determining the results of the t test, namely 0.001 < 0.05, it can be concluded that there is a significant difference between the pre-test value and the post-test value. The value of the n-gain score is categorized as medium with a value of 0.69. From the t-test scores and n-gain scores, it can be concluded that there is a very significant difference in the scores before using the learning video and after using this learning video.